DNA barcoding of new world cicada killers (Hymenoptera: Crabronidae) - Hastings, Jon M.; Schultheis, Patrick J.; Whitson, Maggie; Holliday, Charles W.; Coelho, Joseph R.; Mendell, Angela M. (Zootaxa, 2008)
We are engaged in a comprehensive study of cicada killers (Sphecius spp.), including their behavioral ecology. At one location, we observed interactions among three putative species of Sphecius, and used DNA barcoding to help clarify relationships among them. For this, we sequenced a fragment of the mitochondrial cytochrome c oxidase subunit I gene. During our study, a new taxonomic key of New World cicada killers, based on morphology, was published, and we expanded the barcoding project to test the congruence between barcodes and this key. In general, barcoding evidence supports morphological distinctions among species; sequence divergences between individuals of different species were within the range expected for congeneric Hymenoptera. However, two conflicts between barcoding and morphological evidence were noted. 1) Haplotypes of Sphecius grandis Say fall into two highly divergent clades, suggesting they are cryptic species. 2) Two clades of S. convallis Patton were found, and the sequences of one clade are virtually identical to those of S. speciosus Drury, suggesting that this clade of S. convallis is conspecific with S. speciosus. Alternative explanations are possible for this result, including hybridization and introgression between the two species. We conclude that our DNA barcoding evidence should be interpreted with caution, but that it has generated interesting questions we hope to resolve with field research coupled with analysis of suitable nuclear gene sequences.